Notch signalling mediates reproductive constraint in the adult worker honeybee - Elizabeth J. Duncan (Nature Portfolio, 2016)
In honeybees, pheromones produced by the queen inhibit reproduction by workers and enforce a eusocial division of labour. Here, Duncan, Hyink and Dearden show that this inhibition is mediated by the Notch signalling pathway in the workers' ovaries.